An Assessment of the Need for School Librarianship Courses in India - Tare, Seema (JOURNAL OF INDIAN EDUCATION, 2024)
School librarians as partners in education, contribute to the educational goals of their schools, effectively performing multi-faceted roles. They manage the library’s physical facilities, develop and organise its varied collection and utilise human resources to provide a range of services to the school community. They also play the role of instructor to students and faculty, teaching information and digital literacy, inquiry-based learning, use of technology for teaching and learning and inculcating a habit of reading and lifelong learning. They collaborate with school administrators and teachers in curriculum development, and provide information and library resources for teaching and learning activities. Such librarians have to be nurtured through adequate targeted training to respond to the unique environment of the school library. School libraries have not been given due recognition in India. A few schools have good libraries and librarians trained in school librarianship are lacking. This paper advocates introduction of specialised school librarianship courses at various levels throughout the country for new and practising librarians in schools. Contents and the subjects or skills of such proposed courses are discussed. It is suggested that legislation mandating trained school librarians in all urban and rural schools that will increase the employability aspect of these courses.